SPE Annual Technical Conference and Exhibition 2010
DOI: 10.2118/134269-ms
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Studies on the Effect of Mechanical Cleaning Devices on Annular Cuttings Concentration and Applications for Optimizing ERD Systems

Abstract: In horizontal and highly deviated portions of an Extended Reach Drilling (ERD) well, cuttings beds form on the low-side of the annulus. The bed partially blocks the annulus resulting in excessive pressure loss and a higher equivalent circulating density (ECD) that is exacerbated by the increase in length of the annulus. This condition limits hole-cleaning capabilities. As a result, selecting favorable drilling parameters is not always sufficient to overcome the hole cleaning problem. Recently, the use of downh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…It is believed that, cuttings transported in the annulus are not always affected by a single parameter, but a combination of parameters to ensure efficient hole cleaning [4]. Other studies have also confirmed that increase in fluid velocity results in a decrease in cuttings accumulation in the wellbore [5][6][7]. Ozbayoglu and Sorgun [8] also conducted cuttings transport experiment and developed empirical correlations for estimating pressure losses with the presence of cuttings and drill pipe rotation in horizontal and inclined wellbores.…”
Section: Introductionmentioning
confidence: 98%
“…It is believed that, cuttings transported in the annulus are not always affected by a single parameter, but a combination of parameters to ensure efficient hole cleaning [4]. Other studies have also confirmed that increase in fluid velocity results in a decrease in cuttings accumulation in the wellbore [5][6][7]. Ozbayoglu and Sorgun [8] also conducted cuttings transport experiment and developed empirical correlations for estimating pressure losses with the presence of cuttings and drill pipe rotation in horizontal and inclined wellbores.…”
Section: Introductionmentioning
confidence: 98%
“…Since the 2010s, the application of the hole cleaning device has gradually risen and achieved a remarkable hole cleaning effect. Puymbroeck et al [19][20][21] introduced a compound hole cleaning device with double helix blade small joints. Laboratory experiments and field tests show that the device has excellent cleaning ability of cuttings bed; besides, it improves the degree of hole cleaning by more than 60% and reduces the friction of drilling tools by 30%.…”
Section: Introductionmentioning
confidence: 99%
“…However, using stabilizer greatly reduces annulus area for drilling fluid as well as cuttings transport efficiency. Especially, studies show the outside profile of stabilizers' blade greatly affects cuttings transport [9,10]. Unreasonable blade shape may lead to bad cuttings transport, back flow, repeated fragmentation, and bit balling; all of these issues will decrease ROP, but few studies have been carried out for the influence on cuttings transport efficiency affected by blade type in vertical wells.…”
Section: Introductionmentioning
confidence: 99%